2020
DOI: 10.1093/cid/ciaa1147
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Respiratory Diphtheria Caused by ß-Lactam–Resistant Corynebacterium diphtheriae

Abstract: Background Diphtheria is a potentially fatal respiratory disease caused by toxigenic Corynebacterium diphtheriae. Although resistance to erythromycin has been recognised, β-lactam resistance in toxigenic diphtheria has not been described. Here, we report a case of fatal respiratory diphtheria caused by toxigenic C. diphtheriae resistant to penicillin and all other β-lactam antibiotics and describe a novel mechanism of inducible carbapenem resistance associated with the acquisition of a mobile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…PBP2m is a putative low-affinity PBP, which would explain why it is less affected by beta-lactam antibiotics. Very recently, Forde et al [80] have reported high-level penicillin resistance (MIC > 256 g/L) in C. diphtheriae strain BQ11 and have attributed this phenotype to a penicillin-binding protein located on transposon Tn3503. We found that the pbp2m-containing unit is 99.92% similar to Tn3503, which additionally harbors a helicase (Additional file 4: Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PBP2m is a putative low-affinity PBP, which would explain why it is less affected by beta-lactam antibiotics. Very recently, Forde et al [80] have reported high-level penicillin resistance (MIC > 256 g/L) in C. diphtheriae strain BQ11 and have attributed this phenotype to a penicillin-binding protein located on transposon Tn3503. We found that the pbp2m-containing unit is 99.92% similar to Tn3503, which additionally harbors a helicase (Additional file 4: Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S14). Besides, PBP2m is 100% identical to the PBP from BQ11 and therefore also possesses the V361A alteration (using C. jeikeium as reference) that was hypothesized to confer high-level penicillin resistance [80]. Further studies on the expression of pbp2m in its variable genetic backgrounds are required to understand the observed difference in penicillin resistance levels.…”
Section: Discussionmentioning
confidence: 99%
“…It can be expected that the global SARS-CoV-2 pandemic, which overwhelmed public health systems in many countries, will result in a further increase of diphtheria due to neglected vaccination programs, and also recent military conflicts such as in Yemen, Ethiopia, or Ukraine may interfere with vaccination. Furthermore, antibiotic-resistant strains of C. diphtheriae are increasingly observed [ 28 , 29 ]. Consequently, not only surveillance of cases, but also continuing research focusing on the re-emerging pathogen is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Penicillin and erythromycin have long been the primary treatments for diphtheria, but recent reports describe an increase in resistance against these antimicrobials, potentially posing a problem for diphtheria treatment [17–20]. Several studies have descibed resistance mechanisms against antimicrobials used for the treatment of diphtheria [21–23]. Specifically, erythromycin resistance in C.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have descibed resistance mechanisms against antimicrobials used for the treatment of diphtheria [21][22][23]. Specifically, erythromycin resistance in C. diphtheriae is commonly encoded by the plasmid mediated erm(X) gene [24].…”
Section: Introductionmentioning
confidence: 99%